Cardiac changes associated with vascular aging - Singam, Narayana Sarma V.; Fine, Christopher; Fleg, Jerome L. (Clinical cardiology (Mahwah, N.J.), 2020)
Cardiovascular aging is a complex process of adaptive structural and functional changes over time. With advancing age, the arterial tree thickens and decreases in compliance, resulting in increased pulse wave velocity, systolic blood pressure, and left ventricular afterload. In response to these arterial changes, the myocardium remodels to maintain systolic function and diastolic filling. These adaptive mechanisms are not necessarily pathologic but increase the susceptibility for myocardial ischemia and heart failure in the presence of common age‐associated comorbidities. This article reviews the pathophysiology of cardiovascular aging and discusses therapeutic interventions that may ameliorate these processes.